From Scroll to Sale: How Social Media Marketing Builds Customer Equity Through Brand Experience at Creamsie Whimsie - Brumadyadisty, Garry Brumadyadisty; Edi Mulyadi; Erialdy; Teuku Fajar Shadiq (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the influence of Social Media Marketing Activities (SMMAs) on Customer Equity, with Brand Experience as a mediating variable among consumers of the premium vape product Creamsie Whimsie in Indonesia. The research method used is a quantitative explanatory approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique through SmartPLS 4, based on data obtained from 150 social media user respondents. The results show that SMMAs have a significant effect on Brand Experience and Customer Equity, and Brand Experience is proven to mediate the relationship between SMMAs and Customer Equity. The conclusion of this study confirms that an effective social media marketing strategy can build a strong brand experience and positively impact customer value in the context of the niche market for experience-based FMCG products.   Keywords: Social Media Marketing, Brand Experience, Customer Equity, Premium Vape, PLS-SEM